High triglyceride to high‐density lipoprotein cholesterol ratio and arterial stiffness in postmenopausal Korean women - Chung, Tae‐Ha (J Clin Hypertens (Greenwich), 2019)
The ratio of triglyceride to high‐density lipoprotein cholesterol (TG/HDL) is positively linked to insulin resistance, and it has emerged as an independent predictor of cardiovascular disease. Menopause is characterized by various detrimental metabolic and vascular changes that may lead to high TG with low HDL cholesterol and arterial stiffness. Several epidemiological studies have reported that high TG/HDL ratio has a positive association with arterial stiffness in both adult and adolescent populations; it is not known whether TG/HDL ratio is related to brachial‐ankle PWV (baPWV) in postmenopausal women. Thus, the authors aimed to investigate the association between TG/HDL ratio and arterial stiffness as measured by baPWV in 434 postmenopausal women. The odds ratios (ORs) and 95% confidence intervals (95% CIs) for high baPWV were calculated after adjusting for confounding variables across TG/HDL ratio quartiles using multiple logistic regression analysis. The mean values of meaningful cardiometabolic variables increased with TG/HDL ratio quartiles. The adjusted baPWV (SEs) significantly increased with TG/HDL quartiles: Q1 = 1412 (22.1), Q2 = 1469 (21.4), Q3 = 1482 (21.0), and Q4 = 1505 (21.6) cm/s after adjusting for age, body mass index (BMI), and systolic blood pressure. The OR (95% CI) of the highest TG/HDL ratio quartile as compared to the lowest TG/HDL ratio quartile for high PWV was 2.77 (1.16‐6.63) after adjusting for age, BMI, smoking status, regular exercise, mean arterial pressure, fasting plasma glucose, total cholesterol level, hypertension, log‐transformed C‐reactive protein, and the use of antihypertensive and lipid‐lowering drugs. The TG/HDL ratio was positively and independently associated with arterial stiffness in postmenopausal Korean women.